# Solve for a 45a=54a^2

45a=54a2
Subtract 54a2 from both sides of the equation.
45a-54a2=0
Factor the left side of the equation.
Factor 9a out of 45a-54a2.
Factor 9a out of 45a.
9a(5)-54a2
Factor 9a out of -54a2.
9a(5)+9a(-6a)
Factor 9a out of 9a(5)+9a(-6a).
9a(5-6a)
9a(5-6a)
Replace the left side with the factored expression.
9a(5-6a)=0
9a(5-6a)=0
Divide each term in 9a(5-6a)=0 by 9.
9a(5-6a)9=09
Cancel the common factor of 9.
Cancel the common factor.
9a(5-6a)9=09
Divide a(5-6a) by 1.
a(5-6a)=09
a(5-6a)=09
Divide 0 by 9.
a(5-6a)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
a=0
5-6a=0
Set the first factor equal to 0.
a=0
Set the next factor equal to 0 and solve.
Set the next factor equal to 0.
5-6a=0
Subtract 5 from both sides of the equation.
-6a=-5
Divide each term by -6 and simplify.
Divide each term in -6a=-5 by -6.
-6a-6=-5-6
Cancel the common factor of -6.
Cancel the common factor.
-6a-6=-5-6
Divide a by 1.
a=-5-6
a=-5-6
Dividing two negative values results in a positive value.
a=56
a=56
a=56
The final solution is all the values that make 9a(5-6a)9=09 true.
a=0,56
The result can be shown in multiple forms.
Exact Form:
a=0,56
Decimal Form:
a=0,0.83‾
Solve for a 45a=54a^2

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top